Electrochemical Synthesis of Potassium Titanate Nanowires in Molten Salts with Good Li+-Intercalation Performance. Issue 14 (1st January 2017) - Huang, Shu; Zhou, Min; Wang, Kangli; Cheng, Shijie; Yan, Guoping; Jiang, Kai
Abstract : The novel material K1.35 Ti8 O16 @C was successfully fabricated via an effective, controllable, and cost-effective electrochemical synthetic method and further evaluated as an anode material for lithium-ion batteries (LIBs). This material delivered high reversible capacities of ∼320 mAh g −1 at 50 mA g −1 and excellent long-term cycle stability (135 mAh g −1 after 2000 cycles at 1 A g −1 ) owing to the high electronic conductivity and fast reversible electrochemical Li-intercalation/extraction behavior of the nanowire structure of K1.35 Ti8 O16 .